The Impact of Citizen Journalism on Local Culture and Public Participation: Analyzing Community Engagement and Media Influence - Stephanie, Emma Chaterine (Kampret Journal, 2024)
This research investigates the influence of citizen journalism on promoting local culture and enhancing public participation. Utilizing a mixed-methods approach, the study combines qualitative interviews and quantitative surveys to analyze how citizen journalism impacts community engagement, cultural preservation, and local governance. The findings reveal that citizen journalism significantly increases public participation by democratizing media access, allowing diverse voices to contribute to public discourse, and providing a platform for grassroots reporting. This inclusivity enhances the visibility of local cultural practices and fosters a more engaged and informed citizenry. However, the study also identifies challenges, including the spread of misinformation, lack of professional standards, and the digital divide, which can affect the credibility and effectiveness of citizen journalism. Addressing these challenges is essential for maximizing the positive impact of citizen journalism.